Worship and the reality of God : an evangelical theology of real presence - Davis, John Jefferson (Downers Grove, Ill. : IVP Academic, 2010)
Is God missing from our worship? Obstacles to true worship are not about contemporary or traditional music, electronic gadgetry or seeker sensitivity. Rather it is the habits of mind and heart, conditioned by our surrounding culture, that hinder our faith in the real presence of the transcendent God among his people. Sensing a real need for renewal, John Jefferson Davis offers a theology of worship that uncovers the most fundamental barriers to our vital involvement in the worship of our holy God. His profound theological analysis leads to fresh and bracing recommendations that will be especially helpful to all those who lead worship or want to more fully and deeply encounter the glory and majesty of God. - Publisher.
Introduction : why God has been lost and where we can look to find Him -- God, the church and the self : searching for reality in evangelical worship -- Reality in worship : the real presence of God on Sunday morning -- The Eucharist : meeting the risen Christ at the table -- From ontology to doxology : from theory to practice in worship renewal -- Appendix : theology and practice of worship : selected readings.
Includes bibliographical references and indexes.
Keywords: Public worship; Presence of God